Forum Choice for Terrorism Suspects - Huq, Aziz Z. (2012)
What forum should be used to adjudicate the status of persons suspected of involvement in terrorism? Recent clashes between Congress and the president as to whether the status of terrorism suspects should be determined via Article III courts or military commissions have revived the debate about this venue question. The problem is typically framed as a matter of legal doctrine, with statutory and doctrinal rules invoked as dispositive guides for sorting suspects into either civilian or military venues. This Article takes issue with the utility of that framing of the problem. It argues that the forum question can more profitably be analyzed through an institutional design lens. A key institutional-design decision is whether and when to create jurisdictional redundancy. When, that is, should the existence of overlapping jurisdictions vest the government with a threshold choice of forums or an option to retry a suspect who has been acquitted in an initial process? Jurisdictional redundancy is pervasive. But conventional wisdom suggests that it is unwise. This Article demonstrates, however, that overlap among forums has complex direct and indirect effects on the accuracy and cost of terrorism related adjudication. The Article presents a comprehensive framework for analyzing redundancy by exploring how redundancy influences error rates, system-maintenance costs, externalities, information production, and incentives. Applying this framework, I contend that the conventional wisdom is flawed. Pervasive redundancy has surprising merit in contrast to two leading reform proposals that would eliminate most jurisdictional overlap